Peningkatan Hasil Belajar Siswa Melalui Video Pembelajaran Pada Mata Pelajaran Pendidikan Agama Islam di kelas IV SDN 12 Padang Kubu - Delpi Putri, Melia (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of 4th-grade students at SD Negeri 12 Padang Kubu in Islamic Religious Education (PAI) by using instructional videos. The research method employed was Classroom Action Research (CAR), conducted in three cycles, each consisting of planning, action, observation, and reflection stages. The results of the study showed that in the first cycle, the percentage of students' completion reached 45%, in the second cycle it increased to 60%, and in the third cycle, it reached 80%. This improvement in learning outcomes indicates that the use of instructional videos is effective in enhancing students' academic performance. Instructional videos can capture students' attention and facilitate their understanding of the material, which in turn increases their motivation and learning outcomes. Based on these findings, it is recommended that teachers consider using videos as an alternative teaching method to improve the quality of learning